Progressive loss of anti-HER2 CD4(+) T-helper type 1 response in breast tumorigenesis and the potential for immune restoration - Datta, Jashodeep (Oncoimmunology, 2015)
Genomic profiling has identified several molecular oncodrivers in breast tumorigenesis. A thorough understanding of endogenous immune responses to these oncodrivers may provide insights into immune interventions for breast cancer (BC). We investigated systemic anti-HER2/neu CD4(+) T-helper type-1 (Th1) responses in HER2-driven breast tumorigenesis. A highly significant stepwise Th1 response loss extending from healthy donors (HD), through HER2(pos)-DCIS, and ultimately to early stage HER2(pos)-invasive BC patients was detected by IFNγ ELISPOT. The anti-HER2 Th1 deficit was not attributable to host-level T-cell anergy, loss of immune competence, or increase in immunosuppressive phenotypes (T(reg)/MDSCs), but rather associated with a functional shift in IFNγ:IL-10-producing phenotypes. HER2(high), but not HER2(low), BC cells expressing IFNγ/TNF-α receptors were susceptible to Th1 cytokine-mediated apoptosis in vitro, which could be significantly rescued by neutralizing IFNγ and TNF-α, suggesting that abrogation of HER2-specific Th1 may reflect a mechanism of immune evasion in HER2-driven tumorigenesis. While largely unaffected by cytotoxic or HER2-targeted (trastuzumab) therapies, depressed Th1 responses in HER2(pos)-BC patients were significantly restored following HER2-pulsed dendritic cell (DC) vaccinations, suggesting that this Th1 defect is not “fixed” and can be corrected by immunologic interventions. Importantly, preserved anti-HER2 Th1 responses were associated with pathologic complete response to neoadjuvant trastuzumab/chemotherapy, while depressed responses were observed in patients incurring locoregional/systemic recurrence following trastuzumab/chemotherapy. Monitoring anti-HER2 Th1 reactivity following HER2-directed therapies may identify vulnerable subgroups at risk of clinicopathologic failure. In such patients, combinations of existing HER2-targeted therapies with strategies to boost anti-HER2 CD4(+) Th1 immunity may decrease the risk of recurrence and thus warrant further investigation.